Morphological variability of Bathybdella sawyeri (Hirudinida: Piscicolidae) from hydrothermal vents on the Galápagos Rift and the South East Pacific Rise - Burreson, Eugene M.; Segonzac, Michel (Zootaxa, 2006)
The deep-sea fish leech Bathybdella sawyeri Burreson has recently been collected from two sites on the South East Pacific Rise at approximately14° and 17°S, 2623–2586 m depth. Leeches were obtained from washings of vent mussels Bathymodiolus thermophilus (Mytilidae) and clams Calyptogena magnifica (Vesicomyidae) collected with a grab by a submersible, or were found attached to the cheliped of the crab Cyanagraea praedator (Bythograeidae) collected in baited traps at 14°S. Most individual leeches had morphology typical of B. sawyeri as originally described, with suckers of approximately equal size, but all specimens collected from the crab C. praedator had unusually large oral suckers that were distinctly larger than the caudal sucker. However, internal morphology of the specimens from C. praedator was identical to B. sawyeri on the basis of serial sections; thus all specimens were identified as B. sawyeri. The only previous report of B. sawyeri is from the Galápagos Rift, so these collections extend the range to the South East Pacific Rise.